The impact of liquidity, return on assets, and company growth on stock prices in Manufacturing Companies listed on the Indonesia Stock Exchange - T.F Bastian Sitorus; Mas Intan Purba; Winda Novalina Br Simbolon; Monika E. Siregar; Nur Aliah (Journal of Economics and Business Letters, 2023)
The purpose of this study is to determine the effect of liquidity, return on assets, and company growth on stock prices in manufacturing companies for the period 2018–2021. The population of this study consisted of 42 companies, and the sample consisted of 17 companies, which included manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2021. In this study, the researcher used a quantitative method with multiple linear regression analysis tools. The research data consisted of numbers that would be measured using statistics as a calculation test tool, related to the problem under study to generate a conclusion. Therefore, it can be concluded that liquidity partially has a negative and insignificant effect on stock prices. Return on assets partially has a positive and significant effect on stock prices. And company growth partially has a positive and significant effect on stock prices. And the magnitude of liquidity, return on assets, and company growth on stock prices is 47.8 %.